Disciplining women : Alpha Kappa Alpha, Black counterpublics, and the cultural politics of Black sororities - Whaley, Deborah Elizabeth (State University of New York Press, 2010)
Black Greek-letter organizations offer many African Americans opportunities for activism, community-building, fostering cultural pride, and cultural work within the African American community. Disciplining Women focuses on the oldest Black Greek-letter sorority, Alpha Kappa Alpha (AKA), established in 1908. In this innovative interdisciplinary analysis of AKA, Deborah Elizabeth Whaley combines ethnographic fieldwork, archival research, oral history, and interpretive readings of popular culture and sorority rituals to examine the role of the Black sorority in women's everyday lives and more broadly within public life and politics. The study includes sorority members' stories of key cultural practices and rituals, including political participation, step dancing, pledging, hazing, and community organizing. While she remains critical of the shortcomings that plague many Black social organizations with activist programs, Whaley shows how AKA's calculated cultivation of sorority life demonstrates personal and group-directed discipline and illuminates how cultural practices intersect with politics and Black public life.